Bisalkylthio side chain manipulation on two-dimensional benzo[1, 2-b:4, 5-b′]dithiophene copolymers with deep HOMO levels for efficient organic photovoltaics. (January 2017) - Yu, Jiangsheng; Yin, Xinxing; Xu, Zhongsheng; Deng, Ping; Han, Yingbin; Zhou, Baojing; Tang, Weihua
Abstract: In this study, three copolymers containing bisalkylthio side chain modifying two-dimensional benzo[1, 2- b :4, 5 -b ′]dithiophene (BDT) donor with different electron-deficient acceptors were synthesized. The copolymers were characterized using a combination of thermal analysis, UV–visible spectroscopy, cyclic voltammetry, and theoretical calculations. All copolymers exhibit deep HOMO energy levels from −5.52 eV to −5.60 eV, correspondingly resulting in high V OC . The photovoltaic properties of the copolymers were also studied systematically. The best devices blendingPBDT-DTBTff with PC71 BM exhibited a best PCE of 7.65%, with a V OC of 0.86 V, a J SC of 13.32 mA cm −2 and a FF of 66.8% due to its high hole mobility (1.1 × 10 −3  cm 2  V −1  s −1 ) and facilitated exciton dissociation and charge transport. This work demonstrates an effective method to tune HOMO energy levels of BDT-based copolymers through introducing bisalkylthio side chain into BDT donor. And this result also demonstrates the significance of the interaction and match between donor-acceptor units providing related polymer with suitable band gap and HOMO/LUMO energy levels. Graphical abstract: Highlights: We demonstrated the synthesis of dialkylthiobenzo[1, 2- b :4, 5- b ′]dithiophene based polymers. We demonstrated the electrochemical characterization and molecular simulation of polymers. We demonstrated the enhanced cell performance using solvent additive. We demonstrated the highest PCE of 7.65% forPBDT-DTBTff based OPVs.